ENDOCRINE PATHOLOGY AND ITS CONSEQUENCES IN CHILDREN - Abdurakhmanov Karshi Khalxodjaevich; Fayziev Olim Ayubovich (Journals Park Publishing, 2024)
Data from domestic and foreign literature and statistical observations indicate unfavorable trends in the health of children associated with diseases of the endocrine system, especially diabetes. In general, diseases of the endocrine system occupy a small proportion among the entire range of diseases that children suffer, which does not correspond to the severe social consequences and deterioration in the quality of life of this pathology. New approaches to health assessment based on the determination of preventable health losses and reduction in active life years can identify diseases on which national health systems should focus their efforts.
Keywords: diseases of the endocrine system in children, morbidity, disability, mortality, medical and social consequences of endocrine pathology, health assessment, preventable losses, reduction in years of active life.